-16+5p=-7(-6+8p)+3

Simple and best practice solution for -16+5p=-7(-6+8p)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -16+5p=-7(-6+8p)+3 equation:



-16+5p=-7(-6+8p)+3
We move all terms to the left:
-16+5p-(-7(-6+8p)+3)=0
We add all the numbers together, and all the variables
5p-(-7(8p-6)+3)-16=0
We calculate terms in parentheses: -(-7(8p-6)+3), so:
-7(8p-6)+3
We multiply parentheses
-56p+42+3
We add all the numbers together, and all the variables
-56p+45
Back to the equation:
-(-56p+45)
We get rid of parentheses
5p+56p-45-16=0
We add all the numbers together, and all the variables
61p-61=0
We move all terms containing p to the left, all other terms to the right
61p=61
p=61/61
p=1

See similar equations:

| 4(2x-24)=2(x+30) | | 1/8-3/4x=1/2x | | 5(20x+16=170) | | 24-(4x+5=23) | | b/25-83=86 | | n-0.75=36 | | 2x+13+7x–21+4x=3x+18–34+2x | | 3x+2=x4(x+2) | | 2(4x+5)+10x+6-2x=4 | | -10+x+8-7x=8x-5+9 | | -11-1.4x=21-0.4x | | J-j+4j=8 | | -19=3c+5 | | 30(50x+11)=410 | | -8=-3+x/3 | | -4k+3(-3k-2)=59 | | 3x+2.5/5=7 | | ½x-7=⅓(x-12) | | 6x=8-3x=33 | | -3(x-4)-6=12 | | x-3=1/3(x+6) | | -4+4(5p-2)=2p+3(-4p+6) | | y/3+20=12 | | 9t+3t+t-12t+t=18 | | 20(45x+5=10) | | 75=3(-6r-5) | | x+(x/2)=9/2 | | 5b=45/36 | | 2(p-5)=4(1+p) | | 5+25k=25-k | | w-48/7=6 | | 11m-m=10 |

Equations solver categories